Get active Powassan: developing sport and recreation programs and policies through participatory action research in a rural community context. Issue 2 (14th March 2020) - Rich, Kyle A.; Misener, Laura
ABSTRACT: Participatory action research (PAR) is characterised by processes of community partnership and respectful attempts to address and mitigate power relationships between researchers and those affected by research. Further, these approaches to research seek to not only understand social phenomena within communities but also to affect change or action in and with community members. However, PAR projects are diverse in their theoretical underpinnings and the political economies of their research and action initiatives. These underpinnings are often located on a continuum between the participatory/Freirian and action-oriented/Lewinian ideologies of PAR approaches. In this paper, we reflect on the processes involved in a four-year PAR partnership with a rural community recreation committee located in Central Ontario, Canada. We discuss the process chronologically, including how we acquired and managed resources; developed programs and policies, and; monitored and evaluated outcomes. Drawing from field notes pertaining to the research partnership, we trace the way our research and action initiatives oscillated between these theoretical/philosophical approaches while we attempted to engage in the processes of empowerment and ongoing research and action. While much of the literature describes PAR processes rooted in either a Freirian or Lewinian tradition, we suggest that fluid movement within and between the two was a productive and enriching process. In doing so, we advance the idea of shifting along the PAR continuum as a framework for thinking about the methodological and logistical practices involved in PAR.